The Workings and Effects of Precarious Employment on Black Women Educators in Development Studies: An Autoethnographic Account of an International Fieldtrip. (July 2022) - Schofield, Lilian N.
This observation is an autoethnographic contribution to understand the epistemological complexities of being employed on a precarious contract and challenging racialized abuse in a higher education institution. I ask the following question: What does it mean for precariously employed Black staff to face and challenge racialized acts and have their expertise questioned by students? This observation draws on my experience of teaching and accompanying students on their compulsory overseas field study. A key finding is the implication that precarious employment practices perpetuate inequality in the discipline of development studies by limiting the ability of Black educators to confront or challenge abuse.